Lysosomal cell death pathways: new possibilities for cancer therapy - Jaattela, Marja (Henry Stewart Talks, 2007)
Cell death in cancer, Introduction to the lysosomes and lysosomal cell death, Lysosomal changes in cancer, Siramesine, a drug that targets lysosomes and kills cancer cells in vitro and in vivo
Archived at 2020/08/13